Design, development, and evaluation of an interactive training simulator for teaching hospital information systems - Ghaffari, Faeze (J Educ Health Promot, 2021)
BACKGROUND: In their apprenticeship program, health information technology (HIT) students are deprived of the ample opportunity to work with the hospital information system (HIS). This study aimed to design an interactive simulator for the HIS training and evaluate its effects on the informatics skills of HIT students. MATERIALS AND METHODS: This study was conducted on 16 Bachelor of Science students of HIT at Kashan University of Medical Sciences in 2019. After the functionalities and features of the simulator were determined based on similar existing simulators, expert opinions were received to simulate eight important processes of admission, discharge, and transfer module in HIS. The scores of students’ skills and time taken to perform the processes were recorded and analyzed before and after the educational intervention. After they were trained by the simulator, the students filled out a usability evaluation questionnaire. The data were then analyzed in SPSS version 21. RESULTS: The simulators of health information systems were characterized by interactivity, multimedia applications, practice exercises, tests, and feedback. After the students were trained by the developed simulator, their skills scores improved significantly in 75% (6/8) of the processes, and the timespans of all processes decreased significantly (P < 0.05). The usability evaluation indicated the usability of the simulator was at a “good” level. CONCLUSIONS: According to the study results, using the simulator improves the informatics skills of HIT students in working with HIS. It is recommended that this method also be used in other apprenticeship programs to teach health information systems.